2012
DOI: 10.1029/2011jc007705
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the oceanic control on the amplitude of sea surface cooling induced by tropical cyclones

Abstract: [1] Tropical cyclones (TCs) induce sea surface cooling that feeds back negatively on their intensity. Previous studies indicate that the cooling magnitude depends on oceanic conditions as well as TC characteristics, but this oceanic control has been poorly documented. We investigate the oceanic influence on TC-induced cooling using a global ocean model experiment that realistically samples the ocean response to more than 3,000 TCs over the last 30 years. We derive a physically grounded oceanic parameter, the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
179
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(194 citation statements)
references
References 62 publications
(94 reference statements)
14
179
1
Order By: Relevance
“…This vertical mixing largely results from the intense vertical shear related to the strong inertial currents driven by TCs (Price 1983;Greatbatch 1984;D'Asaro 1985;Shay et al 1989;Price et al 1994;D'Asaro et al 1995;Crawford and Large 1996;Tsai et al 2008;Samson et al 2009;Jullien et al 2012). Recently, Vincent et al (2012a) have confirmed that vertical mixing is the dominant cooling process close to cyclone tracks and for strong cyclones by using an ocean general circulation model to study the cold wake of more than 3000 TCs over the last 30 years. Airsea fluxes (i.e., strong latent and sensible heat fluxes due to intense TC winds) nonetheless contribute in a nonnegligible way along the track of weaker storms, and lateral advection can contribute to up to 15% of the cooling for most intense TCs (Vincent et al 2012a).…”
Section: Introductionmentioning
confidence: 69%
“…This vertical mixing largely results from the intense vertical shear related to the strong inertial currents driven by TCs (Price 1983;Greatbatch 1984;D'Asaro 1985;Shay et al 1989;Price et al 1994;D'Asaro et al 1995;Crawford and Large 1996;Tsai et al 2008;Samson et al 2009;Jullien et al 2012). Recently, Vincent et al (2012a) have confirmed that vertical mixing is the dominant cooling process close to cyclone tracks and for strong cyclones by using an ocean general circulation model to study the cold wake of more than 3000 TCs over the last 30 years. Airsea fluxes (i.e., strong latent and sensible heat fluxes due to intense TC winds) nonetheless contribute in a nonnegligible way along the track of weaker storms, and lateral advection can contribute to up to 15% of the cooling for most intense TCs (Vincent et al 2012a).…”
Section: Introductionmentioning
confidence: 69%
“…While the forecast of a TC's path has improved substantially over the past few decades, the prediction of its intensity remains challenging [Rappaport et al, 2012]. When over the ocean, vertical mixing induced by a TC entrains colder, deeper water into the relatively warm near-surface mixed layer, resulting in a cooling of the sea surface temperature (SST) [Price, 1981;Bender and Ginis, 2000;D'Asaro et al, 2007;Vincent et al, 2012aVincent et al, , 2012b. The decrease in SST is a negative feedback on the TC's intensity through its reduction in the flux of heat from the ocean to the atmosphere [Shay et al, 2000;Cione and Uhlhorn, 2003;Lloyd and Vecchi, 2011;Balaguru et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of a TC is critically dependent on the air-sea enthalpy difference (9). Thus, any process or feature that can affect the TC-induced sea surface temperature (SST) change due to entrainment caused by wind mixing or upwelling (10) may play a role in TC intensification (11)(12)(13), making it critical to understand the factors controlling the upper-ocean response to TCs (14).…”
mentioning
confidence: 99%